2015
DOI: 10.1097/dss.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Errors Leading to Nonmelanoma Skin Cancer Recurrence After Mohs Micrographic Surgery

Abstract: Local recurrences after MMS are extremely rare. When recurrences do occur, they can be attributed to errors in histological interpretation or tumor mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…8,9 Reasons for explaining recurrence after MMS are failure to excise more tissue when a dense inflammatory infiltrate is present, presence of residual tumor at the margins, missing epidermis or dermis, multifocal tumor and wrong inking of the lesion. 10 In our case, recurrence results may also be due to a higher complexity of the tumors (larger, more infiltrative and more aggressive) as more than half of these patients with recurrent disease were complex cases, referred from other centers, mostly persistent/recurrent basal cell carcinomas that needed closure by skin flap or skin graft.…”
Section: Discussionmentioning
confidence: 68%
“…8,9 Reasons for explaining recurrence after MMS are failure to excise more tissue when a dense inflammatory infiltrate is present, presence of residual tumor at the margins, missing epidermis or dermis, multifocal tumor and wrong inking of the lesion. 10 In our case, recurrence results may also be due to a higher complexity of the tumors (larger, more infiltrative and more aggressive) as more than half of these patients with recurrent disease were complex cases, referred from other centers, mostly persistent/recurrent basal cell carcinomas that needed closure by skin flap or skin graft.…”
Section: Discussionmentioning
confidence: 68%
“…Although cure rates with MMS approach 99%, local recurrences do occur . These recurrences may be explained by various factors, including noncontiguous tumors, surgical and histopathological error, incomplete representation of the margins in the Mohs frozen section slides, dense inflammatory infiltrates or fibrosis masking tumor, the occurrence of a new primary tumor in adjacent skin, etc . In our study, four cases of recurrence were found after MMS.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, it’s important to take tissue fully around the mapped tumor positive area to limit the chance of sampling error of the second and subsequent stages. 36 , 37 Once margins are tumor-free, the Mohs surgeon or multi-specialty colleagues can safely reconstruct the wound.…”
Section: Preoperative Considerationsmentioning
confidence: 99%